The campus-masjid convergence in Islam - Hasan, Md. Mahmudul (2018)
In Islam, education is a complete whole in itself that addresses all aspects of human life. Strictly speaking, the term ‘Islamic education’ is non-existent in the Qur’an, while the concept of ilm nafei (beneficial knowledge) is there in the Sunnah. So Islam encompasses in its own structure any knowledge that benefits its recipient as well as others and does not cause injustice (harm) to any. As such, Islam does not recognise the dualism of ‘religious’ and ‘secular’ education. As British writer Marmaduke Pickthall said in a speech he gave in Madras in 1927, “There was no distinction between secular education and religious education in the great days of Islam. All education was brought into the religious sphere.”